Source, transport and fate of terrestrial organic carbon on the western Mediterranean Sea, Gulf of Lions, France - Tesi, Tommaso; Miserocchi, Stefano; Goñi, Miguel A.; Langone, Leonardo (Marine chemistry, 2007)
As part of the EuroSTRATAFORM project, a multi-proxy study was conducted in order to investigate origin, transport and deposition of riverine organic matter in the Gulf of Lions. Surface sediments (0–1 cm) from the Rhône prodelta area and along the sediment dispersal system were collected in September 2004 and in April 2005. Lignin, elemental and stable carbon isotopic analyses were carried out to characterize the source of sedimentary organic material and to facilitate evaluation of temporal and spatial variability. Large contrasts in the organic matter composition of prodelta sediments were observed as a result of the preferential transport of the finest material. In our hypothesis, woody debris, rich in organic matter, hydraulically behaves like very fine sand and is retained within the prodelta area. In contrast, the organic matter adsorbed onto finer particles is selectively transported away from the prodelta along the sediment dispersal system, explaining the distinct organic matter composition observed in the offshore regions.